Effect of Different Cultivation Modes (Photoautotrophic, Mixotrophic, and Heterotrophic) on the Growth of Chlorella sp. and Biocompositions - Yun, Hyun-Sik; Kim, Young-Saeng; Yoon, Ho-Sung (Frontiers in Bioengineering and Biotechnology, 2021)
In the past, biomass production using microalgae culture was dependent on inorganic carbon sources as microalgae are photosynthetic organisms. However, microalgae utilize both organic and inorganic carbon sources, such as glucose. Glucose is an excellent source of organic carbon that enhances biomass yield and the content of useful substances in microalgae. In this study, photoautotrophic, mixotrophic, and heterotrophic cultivation conditions were applied to three well-known strains of Chlorella (KNUA104, KNUA114, and KNUA122) to assess biomass productivity, and compositional changes (lipid, protein, and pigment) were evaluated in BG11 media under photoautotrophic, mixotrophic, and heterotrophic conditions utilizing different initial concentrations of glucose (5, 10, 15, 20, and 25 g∙L−1). Compared to the photoautotrophic condition (biomass yield: KNUA104, 0.35 ± 0.04 g/L/d; KNUA114, 0.40 ± 0.08 g/L/d; KNUA122, 0.38 ± 0.05 g/L/d) glucose was absent, and the biomass yield improved in the mixotrophic (glucose: 20 g∙L−1; biomass yield: KNUA104, 2.99 ± 0.10 g/L/d; KNUA114, 5.18 ± 0.81 g/L/d; KNUA122, 5.07 ± 0.22 g/L/d) and heterotrophic conditions (glucose: 20 g∙L−1; biomass yield: KNUA104, 1.72 ± 0.26 g/L/d; KNUA114, 4.26 ± 0.27 g/L/d; KNUA122, 4.32 ± 0.32 g/L/d). All strains under mixotrophic and heterotrophic conditions were optimally cultured when 15–20 g∙L−1 initial glucose was provided. Although bioresourse productivity improved under both mixotrophic and heterotrophic conditions where mixotrophic conditions were found to be optimal as the yields of lipid and pigment were also enhanced. Protein content was less affected by the presence of light or the concentration of glucose. Under mixotrophic conditions, the highest lipid content (glucose: 15 g∙L−1; lipid content: 68.80 ± 0.54 %) was obtained with Chlorella vulgaris KNUA104, and enhanced pigment productivity of Chlorella sorokiniana KNUA114 and KNUA122 (additional pigment yield obtained with 15 g∙L−1 glucose: KNUA 114, 0.33 ± 0.01 g∙L−1; KNUA122, 0.21 ± 0.01 g∙L−1). Also, saturated fatty acid (SFA) content was enhanced in all strains (SFA: KNUA104, 29.76% ± 1.31%; KNUA114, 37.01% ± 0.98%; KNUA122, 33.37% ± 0.17%) under mixotrophic conditions. These results suggest that mixotrophic cultivation of Chlorella vulgaris and Chlorella sorokiniana could improve biomass yield and the raw material quality of biomass.